2020
DOI: 10.32932/pjnh.2020.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia in Chronic Kidney Disease: a role yet to be explained

Abstract: Hyperuricemia is commonly found in the general population, with a prevalence of about 20 to 25% in adult men and slightly lower prevalence in pre-menopausal women. In both genders, incidence increases with age 1. The prevalence of chronic kidney disease (CKD) has been increasing in the past few years, with its morbidity and mortality not only related to the end-stage renal disease (ESRD), but also with cardiovascular disease. As such, every effort must be made to slow its progression. Emerging evidence suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that soluble SUA exhibits a behavioral duality acting as pro-oxidant within the cell and antioxidant in the extracellular environment [ 3 , 4 ]. The remnant of circulating SUA accounts for more than half of the antioxidant potential of human blood [ 5 ]. However, when it is inside the cells, it exhibits a pro-oxidant behavior [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that soluble SUA exhibits a behavioral duality acting as pro-oxidant within the cell and antioxidant in the extracellular environment [ 3 , 4 ]. The remnant of circulating SUA accounts for more than half of the antioxidant potential of human blood [ 5 ]. However, when it is inside the cells, it exhibits a pro-oxidant behavior [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CKD, the level of SUA may be increased due to decreased excretion capacity of the kidneys [ 7 ]. On the other hand, some studies suggest that hyperuricemia causes renal injury by vasoconstriction mediated by endothelium dysfunction, activation of the renin-angiotensin system and epithelial changes in renal tubular cells [ 5 , 11 ]. SUA may also be associated with the development of CKD through some factors, such as organ toxicity and worsening of risk factors for CKD, such as arterial hypertension (AH) [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…UA is the final product of purine catabolism from exogenous sources, through diet, and endogenous, by cell degradation 10 . The remnant of circulating UA accounts for more than half of the antioxidant potential of human blood 11 . However, when it is inside the cells, it exhibits a pro-oxidant behavior, stimulating the production of free radicals and pro-inflammatory cytokines, reducing the bioavailability of vasodilator substances and increasing vasoconstrictor substances such as angiotensin, which lead to oxidative stress, chronic inflammation and endothelial dysfunction, the tripod of the pathogenesis and progression of CKD 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several mechanisms by which high levels of uric acid increases the risk for CKD development and progression [31,32]: direct toxicity to the kidney; exacerbation of other risk factors for kidney disease, such as hypertension; or by being a marker of the severity of other risk factors, including those attributable to or associated with DM and the metabolic syndrome. In a study in rats, hyperuricemia increased systemic blood pressure, proteinuria, renal dysfunction, progressive renal scarring and induced vascular disease via a cyclooxygenase-2-dependent pathway [33].…”
mentioning
confidence: 99%
“…At the same time despite the vast evidence of an association between hyperuricemia and CKD, there are still conflicting results in clinical studies, with several unanswered questions regarding the role of uric acid as a casual, compensatory or coincidental phenomenon in these patients [32].…”
mentioning
confidence: 99%